ANALISIS PENDAPATAN PETANI JAGUNG (Zea mays L.) DI DESA BENTENG KECAMATAN TERIAK KABUPATEN BENGKAYANG - Youlla, Donna; Riyo, Riyo (Jurnal Ekonomi STIEP, 2023)
The objective of this research was to determine the magnitude of the costs and revenues of corn farming in Benteng Village, Teriak Sub-district, Bengkayang Regency, West Kalimantan. The object of this study was Corn (Zea mays L.). The research location was Benteng Village, Teriak Sub-district, Bengkayang Regency, West Kalimantan. Data collection methods used to support this research included questionnaires, interviews, documentation, observation, and literature review. The data used in this research were primary and secondary data. Primary data were obtained through direct field observations and interviews with farmers, accompanied by questionnaires, while secondary data were obtained from the Agricultural Extension Agency in Benteng Village, Teriak Sub-district, Bengkayang Regency. The data analysis technique employed in this research was descriptive analysis used to determine the costs, revenues, and incomes of corn farming. The population in this research was corn farmers in Benteng Village, Teriak Sub-district, Bengkayang Regency, West Kalimantan. The sampling technique used in this research was Simple Random Sampling, with a sample size of 38 corn farmers. The variable costs in this research amounted to Rp. 2,779,450, covering seeds, fertilizers, pesticides, and equipment rental. The fixed costs in this research were Rp. 12,485, covering the rental of hoes and machetes. The total cost in this research was Rp. 2,791,935, comprising the total variable costs plus the total fixed costs. The revenue obtained by farmers was Rp. 13,889,200 per planting season, obtained from a production volume of Rp. 5,342/kg multiplied by a production price of Rp. 2,600/kg, and the income obtained by farmers was Rp. 11,097,265 per planting season.